EMOTIONAL EDUCATION AND ITS IMPLICATION IN ADOLESCENCE - Regilânia Ferreira Lima, Francisca; Nunes de Sousa, Valdênia; Fernandes Carneiro Marinho Ferreira, Sueli; Camurça Janebro Damasceno, Fabíola; Daniel Silva Brandão, Higor; Correia Rocha Cavalcante, Geane; Duarte Rodrigues, Luzia; Soares Damasceno, Leandro; Cristina Cavalcante Rodrigues Dantas, Ana; Eugênia Ferreira da Silva Leão, Maria (Revista Gênero e Interdisciplinaridade, 2024)
This article has as its title “Emotional Education and its implication in adolescence”, and aimed to present and discuss the main concepts and particularities regarding emotional education and its implication in adolescence. The study provides a reflection on the adolescent’s education and emotional balance, where this is an indispensable element for a more significant coexistence. To this end, the theme cited from the bibliographic research regarding the subject exposed seeks through the authors, to understand that emotional education has been developed in the most varied situations of social daily life and the current socio-political conjuncture and the need for its reach in Life of the teenager.